Local Crystalline Structure of Doped Semiconductor Oxides Characterized by Perturbed Angular Correlations: Experimental and Theoretical Insights - Anastasia Burimova; Artur Wilson Carbonari; Nicole Pereira de Lima; Arnaldo Alves Miranda Filho; Alexandre Pinho dos Santos Souza; Tatiane da Silva Nascimento Sales; Wanderson Lobato Ferreira; Luciano Fabricio Dias Pereira; Bruno Santos Correa; Rajendra Narain Saxena (Crystals, 2022)
Doping semiconductor oxides with trace amounts of non-native elements can improve their properties such as bandgap and conductivity. The lack of local techniques makes the precise characterization of these materials difficult. Among the few techniques capable of providing local characterization, those based on hyperfine interactions at probe nuclei have the advantage of being well established, probing the material homogeneously and completely, thus investigating different regions of material. Some of these techniques are also quite sensitive even at extremely low dopant concentrations. The perturbed angular correlation technique, combined with first-principles calculations, has recently been shown to be a powerful method for characterizing doped semiconductor oxides. In this paper, we present a brief review of the unique information extracted from the semiconductor investigation with such a complex approach, including semiconductor oxides doped with cadmium and other elements. A strong relationship between the local environment, including electronic structure, and the nature of the dopant and the native element of the doped oxides is also shown.